Effects of bisphosphonates on mandibular condyle of ovariectomized osteoporotic rats using micro‐ct and histomorphometric analysis. (21st October 2016) - Jiang, Liting; Shen, Xing; Wei, Li; Zhou, Qi; Gao, Yiming
Abstract : Objective: To evaluate microarchitectural changes in condylar cartilage and associated subchondral bone after bisphosphonates treatment using an ovariectomized (OVX) osteoporosis rat model. Methods: Thirty six‐month‐old female Sprague‐Dawley rats were randomly divided into sham, OVX, and risedronate (RIS)‐treated groups. Both OVX and RIS groups received bilateral ovariectomy. OVX group was treated subcutaneously with saline, whereas RIS group received risedronate treatment (2.4 μg/kg) subcutaneously for 3 months. At the end of 3 months, animals were sacrificed and the entire condyles were harvested for micro‐CT and histological analyses. Immunohistochemistry (IHC) was performed to assess the expression of type I/II collagen protein by semiquantitative imaging analysis. Results: Micro‐CT analysis showed OVX group had significant condylar subchondral bone loss compared to sham as shown by significant decrease in bone volume fraction ( P = 0.028), trabecular thickness ( P = 0.041), and significant increase in trabecular spacing ( P = 0.003). In RIS group, partial inhibition of OVX‐induced bone loss was detected. HE staining showed proliferative layer of condylar cartilage reduced, while hypertrophic chondrocyte layer increased significantly in RIS group compared to sham and OVX groups. IHC showed reduced expression of Col I in both the OVX and RIS groups, whereas expression of Col II was reduced in the OVX group but increased in the RIS group. Conclusion: Our findings suggest that systemic bisphosphonate treatment influences the structure and ossification of condylar cartilage and it has a dual action on condyle in a postmenopausal osteoporosis rat model which raises the concerns for the potential side effects of BPs on condyle to elder patients.